زواج الأقارب بين الشرع والطب: دراسة فقهية مقارنة - محمد، أميرة فتحي عوض Mohammed, Amirah Fathi Awad (جامعة الأزهر - كلية الشريعة والقانون بطنطا, 2018)
اهتم الإسلام بموضوع الزواج وجعله عقد جليل القدر عظيم الشأن. فمن خلال عقد الزواج يتحقق السكن النفسي والمودة والرحمة والطمأنينة. والزواج هو الطريق الوحيد لإنجاب الأولاد الشرعيين وتربيتهم وحفظ الأنساب. ومن العادات والتقاليد والأعراف السائدة في بعض المجتمعات أنها تفضل زواج الأقارب والتركيز بصفة خاصة على الزواج من أبناء العمومة. وذلك بهدف الحفاظ على اسم العائلة، وتقوية وتوطيد العلاقات الأسرية، والمحافظة على الميراث حتى لا تنتقل أموال العائلة من خلال الزوجة إلى شخص أجنبي. وبعض الناس يفضلون تجنب زواج الأقارب نتيجة المشكلات التي تحدث داخل العائلة الواحدة، بسبب اختلاف الزوجين مما يؤدي إلى النزاع والقطيعة فيفضل البعض الابتعاد عن زواج الأقارب. والثابت شرعا أنه لا يوجد نص قطعي في القرآن الكريم ولا في السنة النبوية المطهرة يحث على زواج الأقارب أو ينهى عنه وإنما ترك الأمر للإباحة. وقد ظهر حديثاً كثير من الدراسات العلمية التي تشير إلى أن زواج الأقارب يسبب الكثير من الأمراض الوراثية فما مدى صحة ذلك؟ ولقد حاولت قدر استطاعتي بيان ما يتعلق بحكم زواج الأقارب في الشرع، وبيان آراء الأطباء في زواج الأقارب.
Islam took care of the subject of marriage and made it a great deal of fate. Through the marriage contract, psychological accommodation, affection, compassion and reassurance are achieved. Marriage is the only way to have legitimate children, raise them up and keep the lineage. It is customary in some societies to prefer the marriage of relatives and the special focus on marriage of cousins. In order to preserve the family name, strengthen and strengthen family relations, and preserve the inheritance so as not to transfer family money through the wife to a foreigner. Some people prefer to avoid the marriage of relatives because of problems that occur within the same family, because of the difference of spouses leading to conflict and estrangement, some prefer to stay away from the marriage of relatives. It is firmly established that there is no text in the Qur'aan or in the Sunnah of the Prophetic Sunnah that urges the marriage of relatives or forbids it, but rather leaves it for permissibility. Recently, many scientific studies have shown that marriage of relatives causes many genetic diseases. I have tried as much as I can to make a statement regarding the rule of marriage of relatives in Sharia, and to express the views of doctors in the marriage of relatives.
Keywords: الفقة الاسلامى -- المسئولية الطبية -- زواج الاقارب -- القيم المجتمعية -- العلاقات الاجتماعية